YONUVCHANLIGI KAMAYTIRILGAN IKKILAMCHI PE MAHSULOTLARI OLISH - Lutfullayev, S; Nazarov, F; Nazarov, F (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
All means that increase fire-resistant properties are divided into fire-resistant coatings and compositions that are absorbed into the material being processed.